PENGARUH PELATIHAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. USAHA KIAT PERMATA DI BATAM - Eka Wulandari (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
This study aims to determine the impact of job training and work discipline at PT Usaha Kiat Permata in Batam on employee performance. There is no doubt that job training and work discipline are factors that can affect employee performance. Improving work training and work discipline will have a positive impact on employee performance. The research sample identified 105 employees of PT Usaha Kiat Permata in Batam. The way to gather information for research is by distributing questionnaires to employees. Data analysis methods for diagnostic tools, which include validity, reliability testing, standard assumptions, and hypothesis testing including T-tests and F-tests. The research tool used to process and analyze this analytic data is SPSS version 25.0. The results showed that job training had a positive and significant impact on employee performance. Work discipline does not have a significant impact on employee performance. At the same time job training and work discipline are very effective in improving employee performance.